2016
DOI: 10.1038/srep39746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-flux, low-energy He+ ion irradiation on Ta as a plasma-facing material

Abstract: The goal of this work is to assess Ta as a potential plasma-facing material for future fusion reactors in terms of its response to high-flux, low-energy He+ ion irradiation. Ta samples were irradiated with 100 eV He+ ions at various fluences up to 3.5 × 1025 ions m−2 while simultaneously heated at constant temperatures in the range 823–1223 K. SEM studies show that irradiated Ta surfaces undergo significant morphology changes that have a strong dependence on both ion fluence and sample temperature. Optical ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In physical chemistry sense, He atoms have strong repulsion to W atoms [80,92]. This ultra-low solubility forces He atoms to self-precipitate into small He bubbles [83] that become nucleation sites [90] for further void growth [93] under radiation induced vacancy supersaturations [94], resulting in material swelling [69,86,95] and high temperature He embrittlement [71,96,97], as well as surface blistering [75][76][77][78] under low energy and high flux He bombardment [54,98] at elevated temperatures [99]. This may be mitigated by engineering structures in material which help in outgassing of He.…”
Section: Bubblementioning
confidence: 99%
See 1 more Smart Citation
“…In physical chemistry sense, He atoms have strong repulsion to W atoms [80,92]. This ultra-low solubility forces He atoms to self-precipitate into small He bubbles [83] that become nucleation sites [90] for further void growth [93] under radiation induced vacancy supersaturations [94], resulting in material swelling [69,86,95] and high temperature He embrittlement [71,96,97], as well as surface blistering [75][76][77][78] under low energy and high flux He bombardment [54,98] at elevated temperatures [99]. This may be mitigated by engineering structures in material which help in outgassing of He.…”
Section: Bubblementioning
confidence: 99%
“…To this end, various materials (such as W [47][48][49][50], addition of Rh in W [51], use of bcc Fe [52,53], Ta [54], W-Ta [55], Ta/Fe [56], Pd [57], nanocrystalline Cu [58], SiOC/Crystalline Fe nanocomposite [59], W-K [60], reduced activation steel [61], ferritic [62], ferritic/martensitic steels [63], Be pebbles [64][65][66][67], Be and beryllides [68], graphite, carbon fiber composite [69]) and high Z atoms (Zr, No, Mo, Hf, Ta) [70] have been tested but none proved satisfactory [71][72][73][74]. All show rapid surface degradation exhibiting surface blisters [75][76][77][78] and formation of fuzz [51,[79][80][81][82] or under dense nanostructure [40] after bubble.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, various materials (such as W [47][48][49][50], addition of Rh in W [51], use of bcc Fe [52,53], Ta [54], W-Ta [55], Ta/Fe [56], Pd [57], nanocrystalline Cu [58], SiOC/Crystalline Fe nanocomposite [59], W-K [60], reduced activation steel [61], ferritic [62], ferritic/martensitic steels [63], Be pebbles [64][65][66][67], Be and beryllides [68], graphite, carbon fiber composite [69]) and high Z atoms (Zr, No, Mo, Hf, Ta) [70] have been tested but none proved satisfactory [71][72][73][74]. All show rapid surface degradation exhibiting surface blisters [75][76][77][78] and formation of fuzz [51,[79][80][81][82] or under dense nanostructure [40] after bubble.…”
Section: Introductionmentioning
confidence: 99%
“…Among the first wall candidate materials, tungsten (W) has been widely studied in recent years because of its high melting point, high thermal conductivity, low sputtering yield, no chemical etching with hydrogen (H) and low H retention [1]. However, the main disadvantages such as low temperature brittleness, recrystallization brittleness and irradiation damage hinder the application of W. Recent studies have shown that tantalum (Ta) has a higher flux threshold for ion-induced surface nanostructures than W [2], which will reduce the damage risk to material integrity and contamination of reactor plasma. Due to its high density, high temperature resistance, corrosion resistance, good plasticity at low temperature and moderate elastic modulus [3][4][5][6], Ta has been considered to be a potential material for high temperature applications such as nuclear engineering, aerospace and other fields [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%